Technique for fissile materials detection using electron linac - Barrata, A.; Dovbnja, A.N.; Eran, L.V.; Karasev, S.P.; Kiryukhin, N.M.; Mel’nik, Yu.P.; Ranyuk, Yu.N.; Trubnikov, S.V.; Shljakhov, I.N. (Вопросы атомной науки и техники, 2005)
The possibilities of technique for fissile materials detection using the pulse γ-quantum fluxes generated by electron linac are studied. The technique is based on detection of neutrons escaping from fissile materials after gamma irradiation (technique of delayed neutrons). The diffusion approach is developed for description of spacetime evolution of neutron fluxes inside the prototype system, which is irradiated by external γ-source. The simulation of electromagnetic interaction with matter is performed using the program package GEANT. The feasibility of this technique is proved for the case of plane one-dimensional model for a three-zone homogeneous subcritical assembly consisting of ²³⁵U and ⁵⁶Fe.